2010
DOI: 10.1055/s-0030-1247354
|View full text |Cite
|
Sign up to set email alerts
|

Inadäquate DRG-Vergütung chirurgischer Patienten mit Morbus Parkinson

Abstract: Compensation of surgical therapy in PD patients has significantly decreased within the DRG system, not considering the increased perioperative risk profile of these patients. In times of rising economic pressure, inadequate reimbursement of treatment costs bears the risk of rejection or restriction for patients with concomitant PD in spite of medical indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…Although, this study showed no increased occurrence of complications, typical risk factors, like increased risk for airway complications, urinary tract infection and falls, should be considered for the treatment of MP patients. [7]. Eine ähnliche Selektionierung lag bei Durchführung der vorliegenden Studie an einer Universitätskli-nik auch für die Kontrollgruppe vor mit auch hier bestehender Tendenz zum Vorliegen von multiplen oder schwerwiegenden Nebenerkrankungen.…”
unclassified
“…Although, this study showed no increased occurrence of complications, typical risk factors, like increased risk for airway complications, urinary tract infection and falls, should be considered for the treatment of MP patients. [7]. Eine ähnliche Selektionierung lag bei Durchführung der vorliegenden Studie an einer Universitätskli-nik auch für die Kontrollgruppe vor mit auch hier bestehender Tendenz zum Vorliegen von multiplen oder schwerwiegenden Nebenerkrankungen.…”
unclassified